Ascertainment of Testosterone Prescribing Practices in the VA. Issue 9 (September 2015) - Jasuja, Guneet K.; Bhasin, Shalender; Reisman, Joel I.; Berlowitz, Dan R.; Rose, Adam J.
Abstract : Background: Prescribing of exogenous testosterone is increasing. Because of the risks associated with testosterone, it is important to follow evidence-based procedures when initiating therapy. Objective: We evaluated whether dispensing of testosterone was preceded by appropriate ascertainment of androgen deficiency, and consideration of potential contraindications, in accordance with practice guidelines. Research Design: A cross-sectional study. Setting: All outpatient clinics within Veterans Affairs (VA) during fiscal years 2009–2012 (FY09–FY12). Subjects: A total of 111, 631 men who had not previously received testosterone from VA, and received at least 1 testosterone dispensing during the study period. A 1-year "look-back" period was used to check for diagnostic tests that occurred before the first fill. Measures: Proportion who underwent appropriate diagnostic evaluation of androgen deficiency and ascertainment of contraindications for testosterone therapy during the year before receiving their first testosterone dispensing. Results: New testosterone dispensing in VA increased from 20, 437 in FY09 to 36, 394 in FY12. Only 3.1% of men who received testosterone had 2 or more low (total or free) testosterone levels in the morning, LH and/or FSH level measured, and no contraindications to testosterone therapy. A total of 16.5% did not have their testosterone level checked at all. Among those prescribed therapy, 1.4% had prostate cancer, 7.6% had obstructive sleep apnea, and 3.5% had elevated hematocrit at baseline. Conclusions: Only a small proportion of men receiving testosterone in VA underwent appropriate testing, and some received this therapy despite important contraindications. Promoting a more uniform application of clinical guidelines may facilitate appropriate use of testosterone.